2004
DOI: 10.1016/j.jvs.2004.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic complications after endovascular abdominal aortic aneurysm repair

Abstract: Ischemic complications are not uncommon after EVAR, and may exceed the incidence with open surgical repair. Limb ischemia is most often a result of limb occlusion, and can be successfully managed with standard interventions. Pelvic ischemia often results from atheroembolization despite preservation of hypogastric arterial circulation. Colonic and spinal ischemia are associated with the highest morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(150 citation statements)
references
References 32 publications
3
137
0
6
Order By: Relevance
“…Remaining studies were observational studies of incidence, describing rates of IC specifically after emergency repair, or after aneurysm repair in general, , with no further identification of risk factors [34][35][36][37][38][39][40] .…”
Section: Operative Factorsmentioning
confidence: 99%
“…Remaining studies were observational studies of incidence, describing rates of IC specifically after emergency repair, or after aneurysm repair in general, , with no further identification of risk factors [34][35][36][37][38][39][40] .…”
Section: Operative Factorsmentioning
confidence: 99%
“…Twisting of grafted limbs narrows the lumen and predisposes to thrombosis. It has been reported that a graft extending into the external iliac artery is a high risk factor for occlusion (16). When the graft extends into the external iliac artery, the likelihood of kinking is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel ischaemia in non-complex, non-fenestrated infrarenal EVAR is very rare, whereas colonic ischaemia due to embolization to the inferior mesenteric artery occurs in 1.0-2.9% [4,10]. The occurrence of colonic ischaemia has also been found to be unrelated to the presence of preoperative hypogastric artery occlusion [4].…”
Section: Discussionmentioning
confidence: 99%